2020
DOI: 10.46291/icontechvol4iss2pp15-27
|View full text |Cite
|
Sign up to set email alerts
|

K-Nearest Neighbour Classifier Usage for Permission Based Malware Detection in Android

Abstract: ABSTRACT Android application platform is making rapid progress in these days. This development has made it the target of malicious application developers. This situation provides a numerical increase in malware apps, diversity in techniques, and rise of damage. Therefore, it is very critical to detect these software and escalation the security of mobile users. Static and dynamic analysis, behaviour scrutiny, machine learning methods are used to ensure security. In this study, K-nearest Neighbourhood (KNN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A classification algorithm combined with a feature selection technique should be fast enough to determine results. k-NN is advantageous in producing results faster at a low cost in minimum processing time [43]. The HTs are self-designed in which three trojans are triggered in a sequence with different functionality [31] and secret key leakage type of trojan [32] are implemented in the AES circuit.…”
Section: Performance Analysismentioning
confidence: 99%
“…A classification algorithm combined with a feature selection technique should be fast enough to determine results. k-NN is advantageous in producing results faster at a low cost in minimum processing time [43]. The HTs are self-designed in which three trojans are triggered in a sequence with different functionality [31] and secret key leakage type of trojan [32] are implemented in the AES circuit.…”
Section: Performance Analysismentioning
confidence: 99%
“…In this study, for the 1st and 2nd layers to design the ensemble model, 8 different classifiers were used, namely Random Forest, Logistic Regression, Multilayer Perceptron, Support Vector Classifier, K-nearest neighbor, XGB, Gaussian Naïve Bayes, and Decision Tree, which have different architectural structures and are widely used to solve various problems [25][26][27]. After this, each classifier was tested independently of each other.…”
Section: Classifier Selection For Ensemble Modelmentioning
confidence: 99%
“…An assessment into the future prospects for Android malware detection research based on machine learning was lastly reviewed and shown to provide higher effectiveness. kNN was used by [20] as a scalable and quick machine learning method for the detection of malignant mobile application. The proposed method utilized 5 nearest neighbours and Minkowski as preferred distance metric.…”
Section: Related Workmentioning
confidence: 99%